Dietary fish oil does not influence acute rejection rate and graft survival after renal transplantation: a randomized placebo‐controlled study - Hernández, Domingo; Guerra, Roberto; Milena, Antonio; Torres, Armando; García, Sagrario; García, Candelaria; Abreu, Pedro; González, Antonieta; Gómez, Maria Angeles; Rufino, Margarita; González‐Posada, José; Lorenzo, Víctor; et al. (Nephrology, dialysis, transplantation, 2002)
Background. Dietary fish oil, rich in omega‐3 polyunsaturated fatty acids, decreases TNF‐α, IL‐1β and IL‐2 levels, which may benefit renal transplant recipients. To explore this possibility, we studied the effect of fish oil on the incidence of acute rejection, in situ expression of interleukins (TNF‐α, IL‐1β and IL‐2) and renal function after renal transplantation. Methods. In a double‐blind clinical trial, 86 subjects with no immunological risk randomly received either 6 g/day of fish oil (fish oil group; n=46) or soy oil (control group; n=40) during the first 3 months after transplantation. The mRNA expression of interleukins (TNF‐α, IL‐1β and IL‐2) was determined by RT‐PCR using fine‐needle aspiration during follow‐up (at baseline and the 1st, 2nd and 3rd month after renal transplantation), as well as during acute rejection episodes and after anti‐rejection therapy. The glomerular filtration rate was determined at baseline, and at 1 and 3 months post‐graft by [51Cr]EDTA clearances. Results. The incidence of acute rejection during the first post‐transplant year was similar in both groups (44 vs 47%), as was 1‐year graft survival (86 vs 89%). There were no differences between groups in overall renal expression of interleukins in patients who did not suffer rejections during the study. At rejection episodes, the fish oil group showed a trend toward a lower renal expression of TNF‐α (3.7±6.8 vs 15±18.6 TNF‐α/actin, ratio of arbitrary optical units; P=0.05). In addition, a trend toward a lower IL‐1β expression after therapy was observed in the fish oil group (49.3±54 vs 84.4±59 IL‐1β/actin, ratio of arbitrary optical units; P=0.05). However, the severity of acute rejections (Banff criteria) as well as renal function after anti‐rejection treatment were similar in both groups. Finally, a greater reduction in triglyceride levels was observed in the fish oil group compared with the control group (−6.6±52.7 vs 12.7±40.2%; P<0.05). Conclusions. Treatment with fish oil during the first 3 months post‐transplantation does not influence acute rejection rate and has no beneficial effect on renal function or graft survival.